DEVELOPING AN ASSESSMENT INSTRUMENT FOR INFORMATION TECHNOLOGY PRACTICUM PROGRAM FROM UNIVERSITY’S PERSPECTIVE (Practitioner Research, 2022)
Focusing on having accurate assessment during Information Technology Practicum, this article focuses on improving the assessment instrument, particularly from university’s perspective. The works are motivated by the unsatisfactory feedbacks from industry regarding Practicum performance and assessment. Based on its suitability, combination of Design Science Research methodology and Action Research are adapted to conduct this study. The improved design is focusing on student learning needs and policy by integrating Practicum elements, university’s expectation, and transferable skills expected to be delivered. Emphasises are given on integrating important elements in achieving Practicum learning outcomes. To ensure its readiness for real implementation, the improved instrument has been evaluated involving Practicum stakeholders for three academic semesters. The improved design is believed to be capable measuring Practicum performance accurately in preparing IT graduates to face the industry as stated in IR 4.0.